Integrated inventory ranking system for oilfield equipment industry - Jalel Ben Hmida; Siddharth Parekh; Jim Lee (Journal of Industrial Engineering and Management (JIEM), 2014)
Purpose: This case study is motivated by the subcontracting problem in an oilfield equipment and service company where the management needs to decide which parts to manufacture in-house when the capacity is not enough to make all required parts. Currently the company is making subcontracting decisions based on management's experience. Design/methodology/approach: Working with the management, a decision support system (DSS) is developed to rank parts by integrating three inventory classification methods considering both quantitative factors such as cost and demand, and qualitative factors such as functionality, efficiency, and quality. The proposed integrated inventory ranking procedure will make use of three classification methods: ABC, FSN, and VED. Findings: An integration mechanism using weights is developed to rank the parts based on the total priority scores. The ranked list generated by the system helps management to identify about 50 critical parts to manufacture in-house. Originality/value: The integration of all three inventory classification techniques into a single system is a unique feature of this research. This is important as it provides a more inclusive, big picture view of the DSS for management's use in making business decisions.
Keywords: 650; inventory management; inventory classification methods; ABC; FSN; VED; subcontracting; decision support system